Teacher problems on children with special needs, special intelligence/talents in the learning process - Liani, Helfi; Mardiana, Jeni; Hermaliza, Sephia; Ananda, Sri Devi Fitri; Andriani, Opi (Kepompong Children Centre Journal, 2024)
The declaration of inclusive education that focuses on facilitating the educational needs of children with special needs (ABK) has been running in many areas in Indonesia, especially in big cities such as Jakarta, Yogyakarta, Surabaya, and Malang. However, many problems arise with its implementation. This study aims to determine the problems experienced by the teachers and schools using qualitative methods and an indigenous approach that involved 112 teachers from 18 inclusive schools in Tanjung Agung District Muko-muko Bathin VII as subjects. Data was collected through an open-ended questionnaire and was analyzed by coding techniques. The results showed a wide range of problems faced by the teachers and schools, such as lack of competence in dealing with students with special needs, lack of parental awareness of children with special needs, the number of students with special needs in each class, lack of cooperation of various parties such as professional government and society.